Levels of IL-10 in lambs pre- and post-exposed experimentally to Mycoplasma ovipneumoniae - Ali Hasan Mejbel; Zainab Ismail Ibrahim (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background: Mycoplasma ovipneumoniae is a respiratory pathogen of domestic sheep, mainly, which causes atypical pneumonia and can also predispose to lung infections and recurrent fatal lamb pneumonia outbreaks in subsequent years. Aims: Isolation of M. ovipneumoniae from the suspected pneumonic sheep, induction of an experimental infection in lambs by inhalation and measurement the levels of interleukin-10 (IL-10) in lambs pre- and post- exposure to the bacterium at different days (0, 6, 14, and 28) as well as in vaccinated lambs by ELISA. Materialsand methods: A total of 37 pneumonic adult sheep were subjected to collection of nasal swabs that transported into PPLO broth, and cultured on PPLO agar. The isolates of M. ovipneumoniae were used to preparation of infection solution and vaccine. Then, an overall18 lambs of 5-6 months of age were selected, acclimated and divided randomly into infected and vaccinatedgroups. In infected group, thelambs (No=12) were divided equally into three subgroups; (A): non-infected and non-treated, (B): infected but not treated, and (C)infected and antibiotic-treated.In vaccinated group (No=6), the lambswere vaccinated with two doses at 2 weeks intervals. For serological estimation of IL-10, venous bloodwas collected once from the lambs of infected group at day 28; whereas, it was collected from vaccinated lambs at the 0, 6, 14 and 28 days of vaccination. Results: An overall 13.51%of study sheep were positive to M. ovipneumoniaethat forms distinctive colonies on PPLO AGAR with generally small, appearing as tiny dew drops or resembling fried eggs. Light microscopy revealed blue Dienes staining of the colonies, indicating that they were Mycoplasmas. Oil microscopy showed lavender Giemsa staining of the cell body, with a predominance of spherical and filamentous forms. In the vaccinated group, the findings of IL-10 were elevated significantly (p≤0.0306) in lambs at the 28th day of first-dose vaccination (96.36 ± 3.27 pg/ml) when compared to values of other days; 0 (74.84 ± 3.47 pg/mL), 6 (79.07 ± 2.94 pg/mL), and 14 (74.91 ± 2.18 pg/mL). In infected group, the findings of subgroup B (164.63 ± 532 pg/mL) were elevated significantly when compared to values of subgroups A (82.45 ± 2.06 pg/mL) and C (108.39 ± 4.89 pg/mL). Conclusion: Mycoplasma ovipneumoniae is primarily prevalent in pneumonic sheep. The expression of IL-10 showed differential patterns across variousvaccination times, with variations observed among infected groups. Subsequently, administration of antibiotic had revealed a significant ability to reduce the overexpression of IL-10 in infected lambs. However, furthermore studies to investigate the prevalence of M.ovipneumoniaeor other mycoplasmas by the molecular tools are necessary. Also, the role of IL-10 and other cytokines in various anatomical sites of respiratory tract throughout disease progression need to moreover studies